How To Help Foundations From Being "Madoffed" - Leibell, David T; Johnson, Phyllis Maloney (Trusts & Estates, 2009)
Now is an excellent time for foundation managers and those who advise them to review the laws and latest decisions governing their investment decisions. An investment can subject a foundation and its managers to penalties under both federal tax law and state law. Under federal tax law, investments that jeopardize a foundation's ability to carry out its tax-exempt purposes are subject to a significant excise tax, as are a foundation's excess business holdings. Transactions that are the result of self-dealing are likewise subject to hefty penalties. The Internal Revenue Manual (IRM) lists the following "more recent strategies that deserve close scrutiny:" investment in "junk" bonds, risk arbitrage, hedge funds, derivatives, distressed real estate, and international equities in third world countries. The IRM also highlights guarantees and collateralizations as investment activities warranting close scrutiny. As painful as the penalties can be, it does take some doing for foundation managers to be deemed liable.